Tiger & Bunny. 6 - Sakakibara, Mizuki; Nishida, Masafumi (VIZ Media, 2015)
The NEXT supremacist Jake Martinez has declared that all NEXT should join him in ruling over humanity! After issuing his call to rebellion, he heads for Justice Tower intending to seize it and establish his rule. The heroes find themselves scrambling to confront him as other old enemies appear, and Barnaby, faced at last with the man who murdered his parents, can no longer hold himself back.